Perceived Stress and Its Epidemiological Correlates among First Year Undergraduate Medical Students – An Observational Study - Pawar, Parthavi; Ganganahalli, Praveen; Udgiri, Rekha; Yadavannavar, MC (Indian Journal of Community Health, 2024)
Introduction: Stress is a process where environmental demands exceed an individual’s ability to cope, leading to psychological and biological changes that may increase the risk of illness. In medical training, excessive stress can result in challenges like financial strain, cultural adjustment, depression, reduced concentration, academic dishonesty, and substance abuse. Objectives: This study aims to assess perceived stress levels among undergraduate medical students and correlate them with demographic factors. Materials & Methods: A cross-sectional study was conducted among first-year medical students using the Perceived Stress Scale (PSS). Participants reported their thoughts and feelings over the past month, indicating the frequency of stress-related experiences. Observations: Among 158 students, 84.8% reported moderate stress levels, 8.9% had high stress, and 6.3% experienced low stress. No significant associations were found with habits. Conclusion: Medical students face unique stressors, such as adjusting to new environments, language, and demanding curricula, which significantly contribute to increased stress levels.